2001
DOI: 10.1002/bit.1125
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of single‐chain antibody production in Pichia pastoris using on‐line methanol control in fed‐batch and mixed‐feed fermentations

Abstract: In the last few years the Pichia pastoris expression system has been gaining more and more interest for the expression of recombinant proteins. Many groups have employed fermentation technology in their investigations because the system is fairly easy to scale up and suitable for the production in the milligram to gram range. A large number of heterologous proteins from different sources has been expressed, but the fermentation process technology has been investigated to a lesser extent. A large number of ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 38 publications
2
18
0
5
Order By: Relevance
“…1a). It meant that P. pastoris cells growth could be supported by glycerol or glucose, however, xylanase gene expression driven by AOX1 promoter can’t be induced in glycerol- or glucose-containing medium, which was in agreement with Hellwig’s report [29]. When 0.5% (v/v) methanol was added at 60 h, the xylanase activity increased in the medium whose initial carbon source was glucose or glycerol, and it was always higher than that in the medium with maltose as initial carbon source.…”
Section: Resultssupporting
confidence: 87%
“…1a). It meant that P. pastoris cells growth could be supported by glycerol or glucose, however, xylanase gene expression driven by AOX1 promoter can’t be induced in glycerol- or glucose-containing medium, which was in agreement with Hellwig’s report [29]. When 0.5% (v/v) methanol was added at 60 h, the xylanase activity increased in the medium whose initial carbon source was glucose or glycerol, and it was always higher than that in the medium with maltose as initial carbon source.…”
Section: Resultssupporting
confidence: 87%
“…For both batch and fedbatch cultures, a defined mineral medium adapted from Hellwig et al (2001) was used containing 0.17 g CaSO 4 ·2H 2 O, 2.86 g K 2 SO 4 , 0.64 g KOH, 2.3 g MgSO 4 ·7H 2 O, 0.2 g EDTA, 7.23 g H 3 PO 4 and 0.1 ml of polypropylene glycol (PPG), which were all autoclaved, and 4.35 ml of filter-sterilised PTM1 solution l −1 and 0.87 mg of biotin l −1 , which were added separately. The PTM1 stock solution (Invitrogen 2002) contained 5.0 ml of 69% H 2 SO 4 , 3.84 g CuSO 4 , 0.08 g NaI, 3.0 g MnSO 4 ·H 2 O, 0.2 g Na 2 MoO 4 ·2H 2 O, 0.02 g H 3 BO 3 , 0.92 g CoCl 2 ·6H 2 O, 20.0 g ZnCl 2 and 65.0 g FeSO 4 ·7H 2 O l −1 .…”
Section: Methodsmentioning
confidence: 99%
“…These findings are especially noteworthy because glycerol, glucose, ethanol and acetate have all been shown to support growth of P. pastoris cells without inducing the AOX promoter [16]. For example, Hellwig and colleagues [17] demonstrated glycerol in the culture medium inhibited production of a recombinant single-chain antibody in mixed feed bioreactor cultures, while Inan and Meagher reported that ethanol and acetate repress AOX -driven expression [16]. …”
Section: Introductionmentioning
confidence: 99%